Organization development : a practitioner's guide for OD and HR - Cheung-Judge, Mee-Yan; Holbeche, Linda (London Kogan, 2021)
"Organization Development (OD) is key to ensuring that organizations and their people can adapt to and engage in ongoing change in today's fast-paced and competitive world. How can those responsible for managing change determine the most appropriate course of action for their organization's needs and maximize capability? Written by two of the leading experts in the field, Organization Development is an essential guide to the theories, practices, tools and techniques for achieving success. It explores the role of HR in relation to OD, and connected areas such as organization design, building organizational agility and resilience, and culture change. Alongside international case studies from organizations including Ernst & Young, Nationwide, Lockheed Martin and the University of Sheffield, UK, this revised third edition of Organization Development contains new chapters on building an adaptive culture of learning and innovation and organization health and 'use of self'. With fresh material on digitization, OD in SMEs, and competence profiles, this is an indispensable handbook to understanding, communicating and implementing organization development approaches for both experienced practitioners and students"--
"First published in Great Britain and the United States in 2011 by Kogan Page Limited"--Title page verso.
Includes bibliographical references and index (pages 521-547)
Keywords: Organizational change; Personnel management